2023
DOI: 10.1002/adfm.202302817
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Reprogrammings of Splenic CD11b+ Cells by Nano‐Hypoxia to Promote Inflamed Damage Site‐Specific Angiogenesis

Abstract: Clinical translation of nanoparticles is limited because of their short circulation time, which hampers targeting to prolong therapeutic effects. Angiogenesis is required to regenerate damaged sites under inflammation, and CD11b+ cells turn vasculogenic under hypoxia. As a turning‐point strategy to increase the circulation time, this study explores liposomal targeting of splenic CD11b+ cells, which are gathered in the spleen and move to inflamed sites inherently. Moreover, nano‐hypoxia is strategized as a ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this review, we examine the research on neovascularization conducted over the past decades and discuss in situ reprogramming as an improvement strategy. We also review recent research strategies that apply in situ reprogramming in neovascularization [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we examine the research on neovascularization conducted over the past decades and discuss in situ reprogramming as an improvement strategy. We also review recent research strategies that apply in situ reprogramming in neovascularization [31].…”
Section: Introductionmentioning
confidence: 99%
“…In situ Reprogramming as a Pro-Angiogenic Inducer One research team identified a convergence point by focusing on the spleen to overcome the insufficient dose and complex ex vivo processing issues of EPC therapy while simultaneously addressing the targeting issue of in situ reprogramming [31]. The spleen is an ideal site for in situ reprogramming because it stores a substantial number of monocytes that migrate to areas, such as sites of myocardial infarction, during inflammation [47,48].…”
Section: Introductionmentioning
confidence: 99%